Pain Exposure Physical Therapy versus conventional treatment in complex regional pain syndrome type 1—a cost-effectiveness analysis alongside a randomized controlled trial - Barnhoorn, Karlijn; Staal, J Bart; van Dongen, Robert TM; Frölke, Jan Paul M; Klomp, Frank P; van de Meent, Henk; Adang, Eddy; Nijhuis-van der Sanden, Maria WG (Clinical rehabilitation, 2018)
Objective: To analyze cost-effectiveness of Pain Exposure Physical Therapy compared to conventional treatment alongside a randomized controlled trial (NCT00817128) in patients with complex regional pain syndrome type 1, where no clinical difference was shown between the two groups in an intention-to-treat analysis. Design: Randomized controlled trial with 9 months follow-up. Setting: Patients were recruited from hospitals and general practitioners in the region around a university hospital. Subjects: A total of 56 patients, 45 (80.4%) female, were randomized. About 4 patients in the intervention and 11 patients in the conventional group switched groups. The mean (SD) age was 44.3 (16.6) years, and in 37 (66.1%) patients, the upper extremity was affected. Interventions: Patients received either Pain Exposure Physical Therapy (maximum of five sessions), or conventional treatment conforming with the Dutch multidisciplinary guideline. Main measures: For the economic evaluation difference between the groups in health-related quality of life (quality-adjusted life years (QALYs)), and the clinical outcomes Impairment level Sum Score—Restricted Version and Pain Disability was determined based on the intention-to-treat analysis as well as differences in both healthcare-related costs and travel expenses. Cost-effectiveness planes were constructed using bootstrapping to compare effects and costs. Results: No significant effects were found for QALYs (mean difference = −0.02; 95% confidence interval (CI) −0.10 to 0.04) and clinical outcomes. A cost minimization analysis showed a significant difference in costs between groups. The conventional treatment was 64% more expensive than the Pain Exposure Physical Therapy. Conclusion: This economic analysis shows that Pain Exposure Physical Therapy compared to conventional treatment is cost-effective.